The Labour Party and the world, volume 1: The evolution of Labour's foreign policy, 1900-51 - Vickers, Rhiannon (Manchester University Press, 2004)
This is the first book in a two-volume set that looks at the foreign policy of the Labour Party throughout the 20th century, and into the early years of the new millennium. These books rectify the dearth of literature on both the political ideology and history of Labour's foreign policy. Through an in-depth political history of Labour's foreign policy in the first half of the twentieth century this first volume produces a new theorisation of the nature of the party's foreign policy. It demonstrates that from its inception, the Labour Party has been deeply involved in and interested in international affairs. The book also shows clearly that Labour has provided an important contribution to the development of foreign policy in Britain. The first volume outlines and assesses the early development and evolution of Labour's world-view. It deals with the foreign policy of the Labour Party during a very tumultuous period on the international stage, including the First World War, the Russian Revolution, the Spanish Civil War, the build up to and violent reality of the Second World War, and the start of the Cold War. This highly readable book provides an excellent analysis of Labour's foreign policy during this period, in which Labour experienced power for the first time. It will be of vital use to scholars and students of British political history in the twentieth century, international relations and British foreign policy.
English
Keywords: Political parties; politics; union; labour; socialism; Clement Attlee; Foreign policy; Soviet Union